2 Answers: Choice B and Choice C
The rate of change is 2.
The rate of change is constant.
======================================================
Explanation:
The first point on the left is when x = 1.5 and it has a height of y = 1
The point (1.5, 1) is on the line.
So is the point (3,4) for similar reasoning.
Compute the slope between those points
m = (y2-y1)/(x2-x1)
m = (4-1)/(3-1.5)
m = 3/(1.5)
m = 2
The slope is 2, which is the same as saying the rate of change is 2. This only applies when x > 1 of which the interval 1.5 ≤ x ≤ 3 is a part of.
Since the slope stays at 2 on the interval 1.5 ≤ x ≤ 3, this means we consider the slope to be constant. If the curve bended at all on this interval, then it wouldn't be a constant slope.
Option C:
A triangle that does not have the same dimension as one of the sides of pyramid.
Because....
There is a rectangular Pyramid, which is sliced perpendicular to its base and through its vertex.
A parabolic function's key characteristic is either having 2 x-intercepts or 2 y-intercepts. That is the reason why the standard form of parabolic functions are:
(x-h)^2 = +/- 4a(y-k) or (y-k)^2 = +/- 4a(x-h), where
(h,k) is the coordinates of the vertex
4a is the lactus rectum
a is the distance from the focus to the vertex
This is also called vertex form because the vertex (h,k) is grouped according to their variable.
Since we don't know any of those parameters, we'll just have to graph the data points given as shown in the picture. From this data alone, we can see that the parabola has two x-intercepts, x=-4 and x=-2. Since it has 2 roots, the parabola is a quadratic equation. Its equation should be
y = (x+4)(x+2)
Expanding the right side
y = x²+4x+2x+8
y = x²+6x+8
Rearrange the equation such that all x terms are on one side of the equation
x²+6x+___=y-8+___
The blank is designated for the missing terms to complete the square. Through completing the squares method, you can express the left side of the equation into (x-h)² form. This is done by taking the middle term, dividing it by two, and squaring it. So, (6/2)²=9. Therefore, you put 9 to the 2 blanks. The equation is unchanged because you add 9 to both sides of the equation.
The final equation is
x²+6x+9=y-8+9
(x+3)²=y+1
Answer:
21
Step-by-step explanation:
Use PEMDAS.
6*3=18
18/3=6
22+5=27
27-6=21
1430 miles in 6.5 hours because you multiply 220 by 6.5 and equals 1430miles